'RAINWATER SHOLAWAT': THE THEO-ECOLOGICAL MOVEMENT OF THE JOMBANG COMMUNITY IN COMBATING THE CLEAN WATER CRISIS - Siti Mariyam; A Zahid (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Theo-ecology has long been one of the alternative solutions to environmental problems, including in Indonesia. The Rainwater Sholawat program represents an alternative theological movement aimed at utilizing rainwater as a solution to address the scarcity of clean water sources and flood issues in East Java, particularly in Karangwinongan Village. The purpose of this article is to elucidate the theological movement behind the Rainwater Sholawat program implemented by the Air Kita Foundation in Winongan Jombang Village, East Java. This study was conducted using a qualitative research method. Data collection techniques through in-depth interviews, observations, and literature review. The findings revealed that the religious approach surrounding the Rainwater Sholawat method successfully raised awareness among the residents about the advantages of rainwater as a viable source of clean water. The Rainwater Sholawat Program is implemented through the organization of festivals, educational initiatives, and supportive studies.Teo-ecology telah lama menjadi salah satu alternatif pemecahan masalah lingkungan, termasuk di Indonesia. Program Sholawat Air Hujan adalah salah satu diantara alternatif gerakan teo-ekologi yang berupaya memanfaatkan air hujan sebagai solusi atas minimnya sumber air bersih dan persoalan banjir di Jawa Timur, khususnya di Desa Karangwinongan. Artikel ini bertujuan untuk menjelaskan gerakan teo-ekologi pada program Sholawat Air Hujan yang dilakukan oleh Yayasan Air Kita di Desa Winongan Jombang, Jawa Timur. Penelitian dilakukan dengan menggunakan metode kualitatif. Teknik pengumpulan data melalui wawancara mendalam, observasi, dan telaah Pustaka. Hasil penelitian menunjukkan bahwa pendekataan keagamaan melalui metode Sholawatan Air Hujan mampu menyadarkan warga atas manfaat air hujan sebagai sumber air bersih. Program Sholawatan Air Hujan ini dilakukan melalui penyelenggaraan festival, edukasi dan pendampingan dalam bentuk pengajian.